Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela; Maddau, Lucia; Franceschini, Antonio; Marras, Francesco; Motta, Andrea (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393l
Keywords: Chemical characterization; Diplobifuranylones; Diplodia corticola; metabolites; Phytotoxicity (voyant)

Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela; Maddau, Lucia; Franceschini, Antonio; Marras, Francesco; Motta, Andrea (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393ldoi: 10.1021/np050393lThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Chemical characterization; Diplobifuranylones; Diplodia corticola; metabolites; Phytotoxicity (voyant)

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. - Cordeiro, N; Belgacem, M N; Silvestre, a J; Pascoal Neto, C; Gandini, A (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.
Keywords: Alkaline methanolysis; Chemical characterization; Cork; Molecular weight distribution; Quercus suber L.; suberin

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. - Cordeiro, N.; Belgacem, M. N.; Silvestre, a J.; Pascoal Neto, C.; Gandini, A. (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.
The following values have no corresponding Zotero field: accession-num: 9585884
Keywords: Alkaline methanolysis; Chemical characterization; Cork; Molecular weight distribution; Quercus suber L.; suberin